Measuring Branding Variables that Affect the Brand Choice Intention toward Tourism Destinations in Thailand’s Eastern Coastal Region - Phalitnonkiat, Passarin (Animo Repository, 2024)
A large number of tourists visit Thailand’s eastern coastal regions every year. Brand choice intention is one of the fundamental elements for developing marketing strategies. Therefore, the purposes of this study are to investigate the impact of five brand elements on destination brand loyalty and brand choice intention and to study the relationships among each construct of consumer brand perception by using EFA, CFA, and SEM. A sample of 830 Thai tourists returned paper-based surveys regarding their interests and perceived value. The study found four brand elements that significantly affect brand loyalty and brand choice intention, both directly and indirectly. The four elements include perceived value, interest, brand awareness, and brand image. Based on the results, tourism organizations in Thailand may need to create marketing strategies that define and communicate the perceived values of traveling to the eastern coastal regions. Such strategies can provide long-term attractiveness that could enhance Thailand’s east-coast tourism industry.